Opioid-related deaths before and after COVID-19 stay-at-home orders in Los Angeles County. (1st November 2021) - Kelley, Marcella A.; Lucas, Jonathan; Stewart, Emily; Goldman, Dana; Doctor, Jason N.
Highlights: Fatal opioid overdoses increased from 2019–2020 in. L.A. County. And increased among Non-Hispanic Caucasians after stay-at-home orders began in L.A. County. Fatal opioid overdoses were concentrated in areas with lower educational attainment. Abstract: Background: Opioid-related morbidity and mortality has increased during the COVID-19 pandemic, yet specific information about the communities most affected remains unknown. Our objective is to evaluate decedent-level associations with an opioid-related death following the implementation of stay-at-home orders in Los Angeles County. Methods: This retrospective cohort study used data from the L.A. County Medical Examiner-Coroner to identify opioid-related deaths in 2019 and 2020. We used logistic regression to analyze the change in opioid-related deaths following a 30-day washout period after the start of stay-at-home orders. Independent variables included decedent age, gender, race and ethnicity, heroin or fentanyl present at the time of death, census tract-level education, and a scheduled drug prescription in the year before death. Results: Opioid-related deaths in L.A. County are most common in census tracts where a small percentage of the population has a Bachelor's degree. Following stay-at-home orders, Non-Hispanic Caucasian individuals had significantly more opioid-related deaths than Hispanic individuals (risk ratio (RR): 1.82 [95 % CI, 1.10–3.02]; P < 0.05) after adjusting for age, gender, and heroin or fentanyl use. Racial and ethnic differences in mortality were not explained by census tract-level education or recent scheduled drug prescriptions. Discussion: There has been an alarming rise in opioid-related deaths in L.A. County during 2020. The increase in opioid-related overdose deaths following the onset of COVID-19 and related policies occurred most often among Non-Hispanic Caucasian individuals. Further research on this trend's underlying cause is needed to inform policy recommendations during these simultaneous public health crises.